FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK PADA BANK KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sugiarto Sugiarto; Henny Setyo Lestari (Jurnal Manajemen dan Pemasaran Jasa, 2017)
This study aimed to determined the factors that impact profitability of conventional banking companies listed in Indonesian Stock Exchange for the period of 2006-2015. The number of samples taken in this study was 20 banks with the sampling technique used was purposive sampling. Independent variables in this study are bank size, capital ratio, loan ratio, deposit and asset quality. The dependent variables are return on equity, return on asset, and net interest margin. From the results, bank size, capital ratio and loan ratio have a significant positive effect on ROE, ROA, and NIM. Deposit has a significant positive effect on ROE but has no significant relationship on ROA and NIM. Asset quality has a significant positive effect on NIM but has no significant relationship with ROE and ROA. In application, the bank is expected to continue to increase its size by continuing to increase its assets, and maintains the quality of capital and assets in order not to become the burden of the bank.